Boundedness of the Sublinear Operators on Anisotropic Herz-slice Spaces (European Journal of Pure and Applied Mathematics, 2025)
We will define the idea of  anisotropic  Herz-slice spaces and prove some properties of these spaces. As an application we obtain the bounds for sublinear operator on anisotropic Herz-slice spaces.
Keywords: Herz spaces, slice spaces, Herz-slice spaces, integral operators, atomic decomposition, Boundedness